2021
DOI: 10.1007/s00431-021-04163-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive assessment of liver abnormalities in pediatric Fontan patients

Abstract: Liver abnormalities are well known among long-term survivors of Fontan palliation, which remains the definite surgery for complex congenital heart disease and single ventricle physiology. Pediatric data however are scarce. We assessed the prevalence and degree of liver abnormalities in pediatric Fontan patients through non-invasive investigations suitable for longitudinal follow-up. Thirty-five patients with a median age of 11.8 years (5.2-16.6) and median time since Fontan of 6 years (1.17-13.83) were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…De Bruyne et al [24] reported that the aspartate aminotransferase, alanine transaminase, gamma-glutamyl transferase, and direct bilirubin levels were increased in 12 (34%), 5 (14%), 24 (69%), and 7 (20%) Fontan patients, respectively; the platelet count was decreased in 7 (20%) Fontan patients. Here, we found that the T-BIL level tended to be increased in FALD-HCC patients; it was a useful predictor of FALD-HCC.…”
Section: Discussionmentioning
confidence: 99%
“…De Bruyne et al [24] reported that the aspartate aminotransferase, alanine transaminase, gamma-glutamyl transferase, and direct bilirubin levels were increased in 12 (34%), 5 (14%), 24 (69%), and 7 (20%) Fontan patients, respectively; the platelet count was decreased in 7 (20%) Fontan patients. Here, we found that the T-BIL level tended to be increased in FALD-HCC patients; it was a useful predictor of FALD-HCC.…”
Section: Discussionmentioning
confidence: 99%
“…This provided us an accurate estimate of the number of patients with cirrhosis, since liver biopsy is considered the gold standard. While non‐invasive methods to detect liver fibrosis and cirrhosis are available, their utility in patients post Fontan surgery remains under investigation, with liver biopsy still the most accurate way for diagnosis of cirrhosis in this patient population 29,59–61 . For HCC, we only included cases where HCC was diagnosed histologically, since Liver Imaging Reporting and Data System (LI‐RADS) criteria used for image‐based HCC diagnosis were developed for patients with cirrhosis and chronic HBV and have not been validated in Fontan patients 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Another potential bias is our cohort's subgroup of patients with FALD. Hepatic congestion increases TE values, which could be falsely attributed to fibrosis ( 37 , 38 ). To address this bias, we performed a sensitivity analysis and confirmed the absence of significant differences after excluding 13 children with FALD.…”
Section: Discussionmentioning
confidence: 99%